Assessing the effects of a 660 nm diode laser on crustacean eyes - Rhys A. C. Hague; James E. V. Rimmer; Mark A. James (PLoS ONE, 2025)
Sustainable management of crustacean fisheries requires accurate and timely data for population modelling, but many stocks are data deficient. To address this challenge, a novel device using Class 3R 660 nm diode lasers and Artificial Intelligence algorithms for automated data collection is under development. Whilst the safe use of Class 3R lasers is prescribed for the human eye, equivalent knowledge is required to ensure that lasers of this Class can be used without causing ocular damage to crustaceans. Some countries recognise crustaceans as sentient, thus ocular impacts that could compromise welfare and impair the subsequent survival of sampled specimens could be deemed unacceptable. This study investigates the impact of a prototype laser scanning system on the compound eyes of the white-legged prawn, Litopenaeus vannamei. Histological analysis in a controlled laboratory revealed a correlation between laser exposure and markers of ocular tissue damage, suggesting potential cumulative effects associated with repeated exposure. However, there was indication of pre-existing, underlying baseline alterations in some markers, possibly associated with senescence. Further, observations indicated minimal immediate behavioural effects following single scans, though care is warranted in extrapolating these findings to natural populations and different species under commercial conditions. In an operational context, specimens would only be subjected to a single exposure with a conveyor speed four times faster than that used experimentally, which equates to ~0.05 mW total laser energy. The estimated exposure for a single scan used experimentally was ~0.19 mW. At this level, there is no clear evidence of ocular tissue damage. However, fewer than five repeated exposures at the 6.7 cm/s conveyor speed used experimentally, may result in observable changes in some ocular tissue underscoring the need for cautious protocol development. This research highlights potential biological markers for evaluating photothermal damage in crustacean eyes, which could be used in future studies covering a broader range of commercially significant species.